A study of the development of attitude toward teaching profession. Of the Faculty of Education Kanchanaburi Rajabhat University Academic Year 2558 . - Klungsiri, Waree; Kongkrapan, Mutita (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research The objectives of this research were to study the development of attitudes toward teachers profession of Kanchanaburi Rajabhat University students. When classified by sex, subject, level of education and domicile, the researcher conducted the data collection. There are 255 students in the Faculty of Education, Faculty of Education year 2558.Statistics used in the analysis include one-way ANOVA and one-way ANOVA. The results can be summarized as follows. 1. Results Analysis Development of Attitude toward Teachers of the Faculty of Education, Kanchanaburi Rajabhat University. Very high The most evaluated aspects are attitudes toward teaching process. The least evaluated aspects were attitudes toward expectations for teachers. 2. The results of the study on the development of attitudes toward teachers profession of the students of Faculty of Education, Kanchanaburi Rajabhat University. When classified by gender, education level and domicile, it was found that attitudes towards teachers Faculty members of the Faculty of Education, as a whole, were not significantly different when classified by personal factors. Attitudes towards teaching and learning are different when classified according to gender. There were differences in attitudes towards teacher expectations when classified by gender. And the results. Article history : Received 11 December 2018 Revised 7 January 2019 Accepted 11 January 2019 SIMILARITY INDEX = 0.00